Continuous Adductor Canal Versus Continuous Femoral Nerve Blocks: Relative Effects on Discharge Readiness Following Unicompartment Knee Arthroplasty. Issue 5 (September 2015) - Sztain, Jacklynn F.; Machi, Anthony T.; Kormylo, Nicholas J.; Abramson, Wendy B.; Madison, Sarah J.; Monahan, Amanda M.; Khatibi, Bahareh; Ball, Scott T.; Gonzales, Francis B.; Sessler, Daniel I.; Mascha, Edward J.; You, Jing; et al.
Abstract : Background: We tested the hypothesis that, following unicompartment knee arthroplasty, a continuous adductor canal block decreases the time to reach 4 discharge criteria compared with a continuous femoral nerve block. Methods: Subjects were randomized to either an adductor canal or femoral perineural catheter (2-day ropivacaine 0.2% infusion) in an unmasked fashion. The primary outcome was the time to attain 4 discharge criteria: (1) adequate analgesia; (2) intravenous opioid independence; (3) ability to independently stand, walk 3 m, return, and sit down; and (4) ambulate 30 m. Results: Subjects with an adductor canal catheter (n = 15) reached all 4 criteria in a median of 35 hours (interquartile range, 24–43 hours), compared with 40 hours (interquartile range, 27–69 hours) for those with a femoral catheter (n = 15; Wilcoxon rank sum test: P = 0.46; log-rank test: P = 0.16). However, the percentages of subjects (adductor canal: femoral) who reached the 2 mobilization criteria were 27%:0% on postoperative day (POD) 0, 93%:53% on POD 1, and 100%:73% on POD 2. Of adductor canal subjects, 100% were discharge ready by POD 2, compared with only 73% of femoral subjects ( P < 0.001). Conclusions: Compared with a continuous femoral nerve block, a continuous adductor canal block did not appreciably decrease the median number of hours to overall discharge readiness, yet did decrease the number of discrete days until discharge readiness. These results are applicable to only unicompartment knee arthroplasty and must be considered preliminary because of the limited sample size of this pilot study.